2016
DOI: 10.1186/s13023-016-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular type Ehlers-Danlos syndrome is associated with platelet dysfunction and low vitamin D serum concentration

Abstract: BackgroundThe vascular type represents a very rare, yet the clinically most fatal entity of Ehlers-Danlos syndrome (EDS). Patients are often admitted due to arterial bleedings and the friable tissue and the altered coagulation contribute to the challenge in treatment strategies. Until now there is little information about clotting characteristics that might influence hemostasis decisively and eventually worsen emergency situations.Results22 vascular type EDS patients were studied for hemoglobin, platelet volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
1
20
0
2
Order By: Relevance
“…One description of EDS patients includes co‐occurring joint hypermobility, thin skin, easy bruising, low factor VIII levels, low VWF and associated platelet aggregation defects . More recently, it has been shown that patients with vascular EDS have a platelet dysfunction, although this was studied only in a small cohort of patients and will need to be tested in a larger group of patients . A recent comprehensive study described significant platelet function abnormalities in patients with EDS and the absence of any consistent coagulation defect including thrombin generation …”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 99%
“…One description of EDS patients includes co‐occurring joint hypermobility, thin skin, easy bruising, low factor VIII levels, low VWF and associated platelet aggregation defects . More recently, it has been shown that patients with vascular EDS have a platelet dysfunction, although this was studied only in a small cohort of patients and will need to be tested in a larger group of patients . A recent comprehensive study described significant platelet function abnormalities in patients with EDS and the absence of any consistent coagulation defect including thrombin generation …”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 99%
“…More recently, a study of 25 pediatric patients with hEDS showed that 56% of them had an abnormal bleeding score obtained with the Pediatric Bleeding Questionnaire (based on the BAT‐ISTH), but coagulation and platelet function were not investigated . Another study of 22 patients with vEDS showed platelet aggregation abnormalities in 50% of them, but the laboratory methods used by the authors (rotational thromboelastrometry or Platelet Function Analyser‐100) are less accurate than the light transmission aggregometry used by us, which is the gold standard method for investigating platelet aggregation . Three other studies applied the BAT‐ISTH score to predict platelet dysfunction in patients with bleeding diathesis and suspected inherited platelet function abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is interesting to note that the Ehlers-Danlos syndrome, another connective tissue disease which may be accompanied by aortic dilatation, can be associated with platelet dysfunction [373][374][375]. Platelet dysfunction could be found in Marfan patients as well, analyzed by the Multiplate and PFA 100 tests [353].…”
Section: Platelet Dysfunctionmentioning
confidence: 99%